2018
DOI: 10.1024/0301-1526/a000713
|View full text |Cite
|
Sign up to set email alerts
|

Management of the left subclavian artery during TEVAR – complications and mid-term follow-up

Abstract: Summary:Background: Numerous conditions that affect the boundary between the aortic arch and descending aorta are treated with thoracic endovascular aortic repair (TEVAR). In 40 % of cases, coverage of the left subclavian artery (LSA) cannot be prevented. Subsequently, neurological complications such as stroke or ischemia of the left upper extremity may develop. However, the actual risk of these complications is subject to considerable controversy. The optimal treatment approach, specifi cally the question whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…While Youssef et al, concluded that covering the left subclavian artery without revascularization was justifiable in their cohort. The study included 40 patients who underwent TEVAR with complete coverage of the left subclavian during the procedure, only 2.5% developed critical upper limb ischemia that was in need of revascularization by transposition of the left subclavian artery, 2.5% developed anterior spinal artery syndrome, and none developed new neurological symptoms during follow up [44].…”
Section: Discussionmentioning
confidence: 99%
“…While Youssef et al, concluded that covering the left subclavian artery without revascularization was justifiable in their cohort. The study included 40 patients who underwent TEVAR with complete coverage of the left subclavian during the procedure, only 2.5% developed critical upper limb ischemia that was in need of revascularization by transposition of the left subclavian artery, 2.5% developed anterior spinal artery syndrome, and none developed new neurological symptoms during follow up [44].…”
Section: Discussionmentioning
confidence: 99%
“…Graft-related complications after TEVAR occur in up to 20% of treated patients. 6 Retrograde type-A aortic dissection (RTAAD) following TEVAR and/or HAR is a well-known complication and can occur also several weeks after procedure. 7 In the last 10 year, we experienced only three cases of RTAAD, including the current one.…”
Section: Discussionmentioning
confidence: 99%
“…Thoracic endovascular aortic repair (TEVAR) is a minimally invasive and widely performed procedure used to treat thoracic aortic pathologies [1]. However, when the left subclavian artery (LSA) is involved in the pathology, a more complex surgical approach is required to guarantee the perfusion of the vertebral and brachial arteries [2,3]. In fact, coverage of the LSA has been proven to be associated with a higher of stroke, spinal cord ischemia, and arm ischemia [2].…”
Section: Introductionmentioning
confidence: 99%